2017
DOI: 10.3389/fpsyg.2017.01339
|View full text |Cite
|
Sign up to set email alerts
|

How Knowledge Worker Teams Deal Effectively with Task Uncertainty: The Impact of Transformational Leadership and Group Development

Abstract: The purpose of this paper is to clarify how leadership is able to improve team effectiveness, by means of its influence on group processes (i.e., increasing group development) and on the group task (i.e., decreasing task uncertainty). Four hundred and eight members of 107 teams in a German research and development (R&D) organization completed a web-based survey; they provided measures of transformational leadership, group development, 2 aspects of task uncertainty, task interdependence, and team effectiveness.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…Second, it is defined as "a state physio-psychological sensation, addressing people's perceptions of psychological and physiological states" (Glazer and Beehr, 2005, 469) and includes both, physiological and psychological outcomes of stress. Third, anxiety is especially related to RA across different countries (Glazer and Beehr, 2005) in working environments that are characterized by uncertainty and ambiguity (Leuteritz et al, 2017;Peters et al, 2017). Fourth, it has also been conceptualized as the most proximal response in supervisorsubordinate relationships that is directed internally (Pyc et al, 2016).…”
Section: Anxiety As a Negative Indicator Of Well-beingmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, it is defined as "a state physio-psychological sensation, addressing people's perceptions of psychological and physiological states" (Glazer and Beehr, 2005, 469) and includes both, physiological and psychological outcomes of stress. Third, anxiety is especially related to RA across different countries (Glazer and Beehr, 2005) in working environments that are characterized by uncertainty and ambiguity (Leuteritz et al, 2017;Peters et al, 2017). Fourth, it has also been conceptualized as the most proximal response in supervisorsubordinate relationships that is directed internally (Pyc et al, 2016).…”
Section: Anxiety As a Negative Indicator Of Well-beingmentioning
confidence: 99%
“…RA, which has been linked with multiple indicators of strain, e.g., the frequency of symptoms of depression, generalized anxiety, hyper-alertness (Dobreva-Martinova et al, 2002), and tension/anxiety (Parker and DeCotiis, 1983;Glazer and Beehr, 2005), is prevalent in research organizations (Schulz, 2013), and thus, relevant to our sample that consisted of employees of a research organization. Those knowledge workers are often confronted with uncertain tasks, conflicting priorities, multiple stakeholders, and requirements that may exceed their available resources (Savelsbergh et al, 2012;Leuteritz et al, 2017). At the same time, teams often suffer compositional changes that provoke a change in responsibilities which may, in turn, result as unclear or incompatible (Alcover et al, 2011).…”
Section: Role Ambiguity As a Job Demandmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Wu and Wang (2015) found that the effect of TFL on team proactivity is stronger when the team task variety is higher. Besides, TFL is more likely to emerge and take effect when the environment is unstable, uncertain, or turbulent (Leuteritz et al, 2017). Accordingly, we expect that if the job design offers some degree of variety, TFL might be more supportive to promote employees' career adaptability.…”
Section: The Moderating Role Of Task Varietymentioning
confidence: 99%
“…For another, low task variety provides fewer opportunities for employees to adopt different skills and develop their capabilities (Pan et al, 2018). Employees follow routine methods to work and are less dependent on transformational leaders' effort at motivating their self-efficacy and capabilities (Leuteritz et al, 2017). Thus, the functioning of TFL on employees' career adaptability is restrained when task variety is low (Aggarwal and Krishnan, 2013).…”
Section: The Moderating Role Of Task Varietymentioning
confidence: 99%